2017
DOI: 10.1186/s12879-017-2787-9
|View full text |Cite
|
Sign up to set email alerts
|

Infection by and genotype characteristics of Enterocytozoon bieneusi in HIV/AIDS patients from Guangxi Zhuang autonomous region, China

Abstract: Background Enterocytozoon bieneusi has been increasingly reported to infect humans and various mammals. Microsporidia cause diarrhea in HIV-infected patients worldwide. PCR amplification and sequencing based on the internal transcribed spacer region have been used to describe the genotypes of E. bieneusi and transmission of microsporidiosis.MethodsIn this study, we examined E. bieneusi infection and genotypes in HIV-positive patients in Guangxi, China. Stool specimens were collected from 285 HIV-positive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 59 publications
3
56
1
3
Order By: Relevance
“…A previous study demonstrated the high degree of sequence diversity in the ITS region of E. bieneusi isolates from China (Liu et al. ; Yang et al. ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A previous study demonstrated the high degree of sequence diversity in the ITS region of E. bieneusi isolates from China (Liu et al. ; Yang et al. ).…”
Section: Discussionmentioning
confidence: 93%
“…Genotype CHG19 isolates were first identified in goats, and were subsequently reported in horses and wild boars (Liu et al. ; Qi et al. ; Shi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analyses of the internal transcribed spacer (ITS) regions of the rRNA gene have been widely applied for the detection of E. bieneusi, and this method is becoming the standard tool for E. bieneusi typing [40]. To date, ITS genotyping has contributed to the identification of over 500 genotypes, with 142 genotypes found in humans and 49 genotypes identified both in humans and animals [10,20,23,31,50,55]. These recognized genotypes have been divided into 11 phylogenetic groups (Groups 1-11) for phylogenetic analysis [23].…”
Section: Introductionmentioning
confidence: 99%
“…These recognized genotypes have been divided into 11 phylogenetic groups (Groups 1-11) for phylogenetic analysis [23]. To date, 132 (93.0%) out of the 142 human pathogenic genotypes and 95.9% (47/49) of the zoonotic genotypes belong to Group 1 or Group 2, highlighting the genotypes with public health significance and the nature of cross-species transmission [10, 20,23,31,50,55]. However, genotypes in Groups 3-11 appear more commonly subject to host adaptation [23].…”
Section: Introductionmentioning
confidence: 99%
“…In immunocompetent individuals, E. bieneusi typically causes only self-limiting infections. In immunocompromised patients, however, such as those with Acquired Immune Deficiency Syndrome (AIDS) and organ transplant recipients, E. bieneusi can cause chronic diarrhea and wasting (Khanduja et al 2017;Liu et al 2017;Sant ın and Fayer 2011).…”
mentioning
confidence: 99%